Conservación de piña mínimamente procesada: evaluación de parámetros fisicoquímicos - Vargas Serna, Claudia Liliana; Gonzalez Torres, Vanessa; Ochoa Martinez, Claudia Isabel; Velez Pasos, Carlos (Ingeniería, 2022)
Context: The high consumption of pineapple worldwide requires that the market offer different commercialization alternatives, including minimally processed products. Undesirable changes in the product during storage can be reduced by its processing and packaging conditions. This work aimed to evaluate the effect of the type of packaging, the pretreatment, and the type of cut on fresh-cut pineapple quality parameters. Method: The pineapple was cut into 2 cm cubes and quarter slices of 1,5 cm thickness. Samples were stored in PET containers with or without an absorbent pad. The precooling of the samples was also evaluated. The quality properties of the fruit were evaluated during 14 days of storage. Results. The quarter slices showed less weight loss and maintained their color, vitamin C content, polyphenols, and antioxidant capacity, whereas the cut in cubes showed a better performance in terms of firmness. The use of absorbent pads accelerated the weight loss. Precooling did not show a significant effect in the response variables. Conclusions: The results obtained suggest that it is possible to maintain the quality properties of minimally processed pineapple of the MD2 variety when it is cut in quarter slices and packaged in PET containers, thus preserving the vitamin C content and phenolic compounds.